2021
DOI: 10.1017/s1355617721001363
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Visual Acuity and Cognitive Decline in Older Adulthood: A 9-Year Longitudinal Study

Abstract: Objective: Emerging evidence suggests low vision may be a modifiable risk factor for cognitive decline. We examined effects of baseline visual acuity (VA) on level of, and change in, cognitive test performance over 9 years. Method: A population-based sample of 1,621 participants (average age 77 years) completed a comprehensive neuropsychological evaluation and VA testing at baseline and reassessed at nine subsequent annual visits. Linear regression modeled the association between baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…A recent study concluded that all types of measured visual impairment were associated with a higher dementia prevalence [16], and meta-analysis research confirmed the consistency of the association [17]. Additionally, a 9-year longitudinal study found better visual ability to be associated with better cognitive performance and slower rates of decline on both vision-dependent and vision-independent cognitive tests [18]. In the case of auditory ability, hearing loss was identified as a risk factor for dementia [19,20].…”
Section: Introductionmentioning
confidence: 93%
“…A recent study concluded that all types of measured visual impairment were associated with a higher dementia prevalence [16], and meta-analysis research confirmed the consistency of the association [17]. Additionally, a 9-year longitudinal study found better visual ability to be associated with better cognitive performance and slower rates of decline on both vision-dependent and vision-independent cognitive tests [18]. In the case of auditory ability, hearing loss was identified as a risk factor for dementia [19,20].…”
Section: Introductionmentioning
confidence: 93%